The lichen genus Lepraria Ach. (Stereocaulaceae, lichenized Ascomycota) in Romania - CRISAN, Florin (One Health & Risk Management, 2020)
Introduction. The genus Lepraria includes diffuse or indefinitely delimited species, always sterile, Lendemer (1) naming it „the most unusual member of the sterile lichen crusts”. According to Tonsberg (2), the leprarioid state appeared as an adaptation to a substrate characterized by dry surfaces, in sites with high humidity and low illumination. The thallus is leprose with an entirely sorediate surface. The lack of fruiting bodies has made the lichens from this group among the least known and studied for a long time. The increase in the number of studies on sterile crustose lichens in recent period has led to an increase in the number of accepted species of the genus Lepraria. The information on the genus Lepraria is not uniformly distributed, the current checklist describes only two species, L. caesioalba and L. finkii in Romania. The recent appearance of several studies that indicate the presence in Romania of other species of the genus mentioned, created the motivation of this study. Material and methods. This study is based on material from the Babes-Bolyai University (CL) herbaria in Cluj-Napoca, Romania and literature data. For 13 species, specimens have been examined. Results. The key for the species of genus Lepraria is proposed, adapted from Wirth (3). The species distribution maps in Romania are given. Conclusions. Fifteen Romanian species are revised, Lepraria eburnea, L. ecorticata, L. umbricola were reported from two locations, L. neglecta was found only in one location. Most widely distributed species in Romania seems to be L. finkii and L. membranacea.